POTENSI PENGEMBANGAN WISATA ALAM DI DESA KAPOPO KECAMATAN SIGI BIROMARU KABUPATEN SIGI PROVINSI SULAWESI TENGAH - Maysarah, Ilda; Toknok, Bau; Daeng Massiri, Sudirman (Universitas Tadulako, 2017)
Kapopo Forest Park is part of the Central Sulawesi Grand Forest Park (Tahura), a natural conservation area that functions as a conservation forest. This study aims to investigate the potential of Kapopo Forest Park to be developed as an ecotourism. The study was carried out in Kapopo Village, Sigi Biromaru Sub-district, Sigi Regency, Central Sulawesi. It was conducted for three months, in May – July 2017. The data analysis used the SWOT analysis method while the data were collected through observation, documentation and in-depth interviews with purposive sampling technique. The findings of this study show that Kapopo Forest Park is a potential tourist attraction for its rich biodiversity and beautiful views. The tourists will be exposed to exotic beauty as well as the uniqueness, authenticity and diversity of flora and fauna. The development strategy requires the segmentation support to introduce and promote Kapopo Forest Park as ecotourism and to raise public awareness about conservation efforts.